The mount Circeo and other mythical mountains of the pontine region (Latina, Italia) - Ceruti, Constanza (2019)
The Pontin plains are located in the center of the Italian peninsula, on the Tyrrhenian coast, in the Latina province of the Lazio region. The coastal plains and their wetlands surround mountains and rocky promontories of low altitude and abrupt conformation that project towards the sea. The symbolic dimension of these mountains is linked to mythical figures of the Greco-Roman world, such as the hero Ulysses, the god Jupiter and the sorceress Circe. Mount Sant´ Angelo that dominates the city of Terracina has at its top the ruins of an important Roman temple dedicated to Jupiter (or Venus) that was reused as a monastery by Benedictine monks. For its part, the Circeo massif offers at its summit the remains of a small temple, which is associated with the figure of the mythical sorceress Circe, which is said to have seduced and retained Ulysses, turning his companions into pigs. The morphology of the mountain profile itself is interpreted as the face of the sorceress, in which the main peak of the massif occupies the place of the nose. This anthropological field research - based on ascents and informal interviews - sheds light on the articulation of the mythical dimension of Mount Circeo and Mount Sant’Angelo de Terracina with tourism and the cultural landscape of the Pontine region.